Two cases of Leclercia adecarboxylata septic arthritis in immunocompetent paediatric patients. Issue 2 (28th February 2022) - Arasu, Ramesh; Ewe, Yean Hsiang; Sundaram, Abavasankar; Foley, David Anthony; Campbell, Anita Jane; Fletcher, Timothy Robin William; Palasanthiran, Pamela; Suzuki, Arnold
Abstract : Leclercia adecarboxylata is a rare cause of septic arthritis in children, and has intrinsic resistance to common antibiotics. We describe two cases of L. adecarboxylata septic arthritis in children that required re-presentation to hospital with prolonged treatment, and highlight the importance of considering L. adecarboxylata as a potential cause of infection among children with penetrating injuries and associated environmental exposure.